AVALIAÇÃO DA APRENDIZAGEM ESCOLAR: do fazer mecânico à intencionalidade teórico-metodológica emancipatória - Azevedo, Raquel de Moraes (2007)
This dissertation intends to analyze the evaluative process in its relationship with the warranty of learning with emancipation feature, starting from the pedagogical quality of the diagnoses of limits and progresses and of the nature of the didactic-methodological interventions carried out by teachers in initial grades of a public network municipal school in Imperatriz - urban area. Starting from qualitative referential by making use of the techniques: semi-structured interview, observation, documental analysis, mixed questionnaire, with the purpose of characterizing the conceptions that prevail among the researched teachers as for the education, learning, methodology, evaluation of learning, student and teacher. It also intends to analyze the correlation of those conceptions amongst themselves and of them with the pedagogical practice, as well as the teachers' work plans, the evaluation instruments with respect to the elaboration, correction and redelivery forms, regarding to investigate if such elements configure a diagnosis-procedural evaluation and yet contemplate the implications of the teachers' objective conditions in the researched school for the action-reflection-action exercise, towards the improvement of the pedagogical practice. Permeating the discussions around the evaluation in its qualitative sense, are Vasconcellos, Hoffmann, Demo and Saul s ideas, which together with authors like Vygotsky and Giroux provide the bases for the analysis of the object in study. By the run course, some verifications became evident in the conceptions and investigated teachers' practices: the conceptions of the subject of the research present different epistemological focuses, several times a same concept is structured starting from divergent approaches amongst themselves. However, they can indicate, more than incoherence, once the rupture with a given referential isn t felt at once, but by successive approaches. When revoked with the methodological point of view, even if in the level of the speeches, it is noticed in most cases, difficulties to establish correlation between the concept and its materialization, above all when this already locates itself in a critical referential. When confronted with the practice, through direct observation and documental analysis, the dissonances between concepts of critical-transformer content and the teacher s effective action are enlarged, committing the diagnosis-procedural dimension of the evaluation. In spite of the noticed predicaments there are some initiatives that they are already characterized by the student's daily attendance by occasion of the room activities, mediated by the dialogue, in the perspective of capturing the hypotheses that the students are having concerning the contents, altering the classic form of facing the mistakes. In smaller scale, but no less important certain debureaucratization of the evaluation is noticed, whereas the students have the opportunity to redo activities, above all production of texts, approaching this way the established criteria. Considering the objective conditions, above all the ones that refer to the teacher's right as for the continuous development in school and especially in the network, although they don't immobilize a pedagogical and evaluative practice of emancipation tendency, because there is always space for resistance, they commit their desire and even the initiative already implemented by some of the subjects in that sense. Before that, one proposes that the Educator's work, that is still differentiated in the network by the supervisor and educational orientation functions, be ruled by the perspective of the research of the pedagogical work, subsidizing this way the teachers in the epistemological field, in which is believed lies the origins of the main observed fragilities, overcoming the pedagogical activism, what naturally implicates the warranty of the processes of continuous development of quality for the educators' group, including the Pedagogue, besides the enlargement of the number of those professionals.